First Report of Umbaspis regularis (Newstead, 1911) (Hemiptera: Diaspididae) Associated with Agonandra brasiliensis Miers ex Benth. & Hook.f. (Opiliaceae) in the Brazilian Cerrado - de Castro, Marcelo T.; Montalvão, Sandro C. L.; Wolff, Vera Regina S. (Entomological Communications, 2022)
Agonandra brasiliensis Miers ex Benth. & Hook.f. (Opiliaceae), popularly known as “pau-marfim” or “cerveja de pobre”, is a tree species of the Brazilian Cerrado and it’s used for timber and medicinal purposes by the local population. Studies about insects associated with A. brasiliensis are inexistent and there is no report of scale insects association with this tree species. This study aimed to report, for the first time, the occurrence of Umbaspis regularis (Newstead, 1911) (Hemiptera: Diaspididae) on A. brasiliensis in Brasília, Distrito Federal, Brazil. This is also the first report of this scale insect in Central Brazil. Additionally, macroscopic and microscopic descriptions of U. regularis and the injuries observed in the plants are also presented.